Implementation Of Google Site As A School Administration System (A Case Study At UPT SMP Negeri 3 Baebunta, North Luwu Regency) - Kaharman; Chalid Imran Musa; Ed. Farida (International Journal of Education, Vocational and Social Science, 2025)
This research aimed to (1) analyze and describe the implementation of Google Site as a school administration system, and (2) identify the supporting and inhibiting factors of its implementation at UPT SMP Negeri 3 Baebunta. The background of this study is the need for the transformation of school administration from a manual and fragmented system to an integrated digital system to enhance efficiency, transparency, and accountability. This study used a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and documentation with the school principal, vice principal for curriculum, head of administration, school operator, and P5 coordinator. The research findings indicate that the implementation of Google Site successfully designed a centralized and integrated digital administration platform, serving as a "one-stop portal" that integrates various Google Workspace services. This platform addresses the school's real needs for centralizing teaching materials, archiving personnel data, standardizing data collection workflows, and publishing the P5 flagship program. The main supporting factors for its success were (a) full support from leadership legitimized by official policy, (b) the availability of adequate infrastructure, (c) the potential of human resources with the presence of early adopters, and (d) a real, felt need from stakeholders. The primary inhibiting factors were non-technical, namely (a) psychological resistance to change from some senior teachers, and (b) the challenge of maintaining long-term user motivation. It is concluded that the implementation of Google Site has successfully transformed the school administration system. This success was driven by a synergy of strong supporting factors, while the main human-centric challenges can be overcome through continuous support via the school's Learning Community (Kombel)